Ideologemes of the Divine Establishment of Imperial Power in the Memorial Sermon of Orthodox Clergy of the Central Chernozem Region’s Dioceses on the Day of Remembrance of the Royal Family Rescue on October 17, 1888 - Konstantin V. Kozlov (Вестник Екатеринбургской духовной семинарии)
The article deals with the constructing of the ideologemes of the divine origin of Imperial authority in Russia at the end of the 19th — beginning of the 20th century in the homiletic practice of Orthodox clergy and their broadcasting in public in connection with the annual celebration on October 17 of the memorable day of the salvation of Emperor Alexander III and his family in the train crash of 1888. The circumstances of this incident contributed to its conceptualization in the Orthodox homiletic thought as a miraculous salvation of the Royal family and, accordingly, the God chosenness of the Emperor and his heirs. The idea of the Divine establishment of the Imperial power in Orthodox homiletics was additionally actualized by the internal political events in Russia in the late 19th — early 20th centuries caused by the country’s modernization and society’s transformation. In this regard, the conceptualization of the ideologemes was the Church’s response to the existing demand for the consolidation of the power and society. The ideologemes were broadcast in public by means of the memorial sermon, a type of thematic sermon. The latter’s creation was associated with the annual church celebration on October 17 of the memorable day of Emperor Alexander III’s and his family rescue. This process has been analyzed on the basis of homiletic monuments created by Orthodox bishops and clergy of the Central Chernozem region’s dioceses and published in the diocesan gazette. According to the church and administrative division of that time the region included Voronezh, Kursk, Oryol and Tambov dioceses. As a result of the analysis of these texts, the following ideologemes were identified: «the miraculous salvation of the Royal family», «the special care of the God over Russia», «the second election of the Romanov dynasty», «October 17 as the day of the ”two gifts of God”». The sermons, which were part of the church commemorative practices, were particularly relevant because this day became a landmark for the last two reigns due to the chronological coincidence with the end and beginning of the emperors’ reign on October 20–21, 1894. This day also marked the beginning of a new stage in the political life of Russia on October 17, 1905.